STRATEGIC BUSINESS MODEL ANALYSIS FOR INTERNATIONAL LNG TRADING MARKET BUSINESS ENTRY OF NATIONAL GAS COMPANY (NGC) - Gerra Maulana; Pri Hermawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
PT National Gas Company Tbk (NGC), as Indonesia’s Subholding Gas under One Energy Group, faces a structural inflection point. Although revenue remained broadly stable, the company’s full-year net profit fell by about 37 percent year-on-year, from approximately USD 340 million in 2024 to USD 215 million in 2025. This margin compression reflects a structural mismatch between maturing upstream pipeline supply in western Indonesia, the company’s growing reliance on LNG to backfill domestic demand, and the price ceilings imposed by the Specified Natural Gas Price regulation on certain industrial sectors. To re-anchor growth, NGC’s Gas Supply & LNG Trading (GSLT) division has begun engaging in international LNG trading, however, the company’s initial 2023–2024 entry under early counterparty arrangement has produced volatile financial outcomes and material legal exposure. An unstructured trading posture is therefore unsustainable, and a structured analytical evaluation of business model alternatives is required. This research addresses three interconnected questions: (1) what factors influence a company’s ability to engage effectively in LNG trading; (2) how common LNG trading business models differ in their key characteristics and trade-offs; and (3) which business model represents the most suitable strategic fit for NGC given its internal capabilities, external risks, and corporate planning constraints. The study adopts a combine qualitative and quantitative methodology, anchored in the Kepner–Tregoe Decision Analysis logic and operationalised through an integrated analytical framework combining Resource-Based View and VRIO for internal analysis, PESTEL and Porter’s Five Forces for external analysis, business model archetype mapping, and Multi-Criteria Decision Analysis (MCDA) using the Analytic Hierarchy Process to rank alternative business models. Primary data come from semi-structured interviews with 12 respondents: 6 internal NGC stakeholders and 6 external stakeholders. Secondary data include NGC’s RJPP (Long-Term Corporate Plan) 2025–2035 LNG Trading projection, FY 2024 and 2025 financial disclosures, regulatory instruments, and industry reports. The internal analysis identifies NGC as fundamentally asset-strong but capability-constrained, physical infrastructure and the embedded role as Indonesia’s national gas aggregator are valuable, rare, and difficult-to-imitate resources, whereas trading capability, front-to-back-office structure, financial-risk hedging, and shipping control are underdeveloped. The external analysis identifies a mixed environment of opportunity and constraint. The MCDA evaluation, weighted by managerial-judgement criteria of strategic fit, financial robustness, risk exposure, capability requirement, implementation complexity, policy alignment, and time-to-market, ranks the hybrid asset-backed portfolio model as the most suitable strategic posture for NGC, ahead of utility/single-buyer, asset-backed integrated, pure portfolio, and merchant-trader archetypes. The ranking is robust under three sensitivity scenarios (One Energy Group–NGC novation completion, restrictive LNG export–import permits, and base-case continuity). The research recommends a phased implementation, a 0–12-month foundation phase to consolidate trading governance and front-to-back-office structures, a 1–3-year anchor build-out integrating novated One Energy Group LNG cargoes and securing shipping and regasification optionality, and a 3–5-year regional scale-up serving Southeast Asia’s emerging. The framework is intended as a decision-support tool to be revisited as market conditions, regulatory frameworks, and NGC’s capability base evolve.